2011
DOI: 10.3747/pdi.2009.00264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Icodextrin and Glucose Solutions for Long Dwell Exchange in Peritoneal Dialysis: A Meta-Analysis of Randomized Controlled Trials

Abstract: ♦ Background: Icodextrin is widely used in peritoneal dialysis (PD); however, the safety and efficacy of icodextrin are unclear. In the present study, we performed a systematic review of randomized controlled trials (RCTs) that compared icodextrin and glucose for the once-daily long dwell in PD. ♦ Methods: Electronic searches were performed in MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials to select all eligible studies. Eligible studies, as determined by consensus using predefined cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 36 publications
2
54
0
3
Order By: Relevance
“…There are no randomized controlled trials of smoking vs non-smoking, but since there is over whelming evidence in the general population to suggest that smoking is harmful, it is unlikely that there ever will be a randomized controlled trial in PD patients. RATIONALE: In 3 recent meta-analyses, an increase in peritoneal ultrafiltration volume as well as a reduction in episodes of uncontrolled fluid overload were observed with the use of icodextrin compared with conventional glucose PD solutions (27)(28)(29)30). The effect of icodextrin was most pronounced in patients with high/high-average transport state.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…There are no randomized controlled trials of smoking vs non-smoking, but since there is over whelming evidence in the general population to suggest that smoking is harmful, it is unlikely that there ever will be a randomized controlled trial in PD patients. RATIONALE: In 3 recent meta-analyses, an increase in peritoneal ultrafiltration volume as well as a reduction in episodes of uncontrolled fluid overload were observed with the use of icodextrin compared with conventional glucose PD solutions (27)(28)(29)30). The effect of icodextrin was most pronounced in patients with high/high-average transport state.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Extraneal PD solution contains icodextrin (a polymer with an average molecular weight of 17,000 Da) as a colloid osmotic agent. Because of its large molecular weight, icodextrin is absorbed less into the systemic circulation and hence, less likely to cause systemic side effects (4). It has been reported that the long-term exposure to a pH neutral Balance PD solution causes less peritoneal inflammation and has a minimal effect on vasoregulation (5)(6).…”
mentioning
confidence: 99%
“…In several studies, a tight association has been observed between elevated serum phosphorus and mortality (1,2).…”
Section: Associations Of Fibroblast Growth Factor 23 With Parameters mentioning
confidence: 99%
“…It is used by more than 10 000 peritoneal dialysis (PD) patients worldwide because it provides sustained positive net ultrafiltration during the long dwell and better metabolic control than that provided by glucose-based solutions, especially in diabetic PD patients (1,2). Furthermore, positive associations with patient and technique survival have been demonstrated for icodextrin (3).…”
mentioning
confidence: 99%